The Need for a Warming Trend A Survey of the School Climate for Pregnant and Parenting Teens - Nash, Margaret A.; Dunkle, Margaret; Equality Center, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This study identified policies, practices, and attitudes that help or hinder continued schooling by pregnant and parenting teenagers. It examined the degree to which schools' treatment of pregnant and parenting students complied with Title IX of the Education Amendments of 1972 and how schools have initiated steps on their own to encourage pregnant and parenting teenagers to stay in school. Twelve diverse schools across the country were surveyed. The findings revealed that few schools had clear policies about how to treat pregnant and parenting students. Nine of the 12 schools were found to have Title IX violations. None of the schools, however, used pregnancy or parenthood as a reason for expulsion or suspension and none required pregnant or parenting students to enroll in special programs rather than staying in the regular classroom. Some schools reported having special initiatives to help pregnant and parenting teenagers stay in school. This report describes the study methodology and sample and lists Title IX problems which were found. It discusses key findings in the areas of attitudes toward pregnant and parenting teenagers, attendance, courses and programs, child care, working with other agencies, health services, extracurricular activities, and counseling and financial aid. Under each subject area are policies and practices that determine the school climate for pregnant and parenting students. (NB)
Availability: Equality Center, 1223 Girard Street, N.W., Washington, DC 20009 ($10.00).
Sponsoring Agency: Women's Educational Equity Act Program (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Attendance; Attitudes; Compliance (Legal); Day Care; Early Parenthood; Educational Environment; Elementary Secondary Education; Extracurricular Activities; Federal Legislation; Health Services; Pregnant Students; School Activities; School Counseling; School Policy; Student Financial Aid; Reports, Research